An Assessment of Ghana’s Twi Language Medical Advertisements - Asuamah Adade-Yeboah, Ginn Bonsu Assibey, Confidence Atakro & (Covenant Journal of Communication, 2019)
Health-related advertisements are aired daily on the radio in Ghana, many of them in local languages. However, little is known if these advertisements fulfill the conditions stipulated by the country’s authorities. This paper assesses the contents of six commercials in the Twi language on two radio stations - Adehyee FM and Hello FM - using the stipulations of Ghana Food and Drugs Authority (GFDA) as a guide. The English transcripts of the spot commercials were produced and analyzed within the relevant theoretical confines. The results show that none of them has fully aligned with the relevant rules and regulations as each recorded only a 50 percent compliance rate during the investigation. To counter this challenge, a new stakeholder assessment model, that makes everyone in the value chain of advertisement production relevant, is proposed.